2002
DOI: 10.1073/pnas.122228699
|View full text |Cite
|
Sign up to set email alerts
|

Increased ionizing radiation sensitivity and genomic instability in the absence of histone H2AX

Abstract: In mammalian cells, DNA double-strand breaks (DSBs) cause rapid phosphorylation of the H2AX core histone variant (to form ␥-H2AX) in megabase chromatin domains flanking sites of DNA damage. To investigate the role of H2AX in mammalian cells, we generated H2AX-deficient (H2AX ⌬/⌬ ) mouse embryonic stem (ES) cells. H2AX ⌬/⌬ ES cells are viable. However, they are highly sensitive to ionizing radiation (IR) and exhibit elevated levels of spontaneous and IR-induced genomic instability. Notably, H2AX is not required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
420
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 492 publications
(458 citation statements)
references
References 41 publications
29
420
1
2
Order By: Relevance
“…Based on its very early appearance, it was assumed that g-H2A.X is a very early response to DSBs and, hence, required for the recruitment of DSB signaling and repair proteins to the sites of DSBs. This hypothesis was supported by data showing that the accumulation in DSB repair foci of numerous repair proteins including 53BP1, BRCA1, and MDC1 is impaired in H2A.X null cells [Bassing et al, 2002;Celeste et al, 2002;Fernandez-Capetillo et al, 2002;Stewart et al, 2003]. In contrast, another study from the Nussenzweig lab showed that H2A.X is dispensable for the initial recruitment of these proteins to the sites of DSBs in MEFs lacking H2A.X expression [Celeste et al, 2003b].…”
Section: C-h2ax and The Dsb Responsementioning
confidence: 90%
“…Based on its very early appearance, it was assumed that g-H2A.X is a very early response to DSBs and, hence, required for the recruitment of DSB signaling and repair proteins to the sites of DSBs. This hypothesis was supported by data showing that the accumulation in DSB repair foci of numerous repair proteins including 53BP1, BRCA1, and MDC1 is impaired in H2A.X null cells [Bassing et al, 2002;Celeste et al, 2002;Fernandez-Capetillo et al, 2002;Stewart et al, 2003]. In contrast, another study from the Nussenzweig lab showed that H2A.X is dispensable for the initial recruitment of these proteins to the sites of DSBs in MEFs lacking H2A.X expression [Celeste et al, 2003b].…”
Section: C-h2ax and The Dsb Responsementioning
confidence: 90%
“…These nuclear micro-domains are thought to contain hundreds to thousands of molecules that accumulate in the vicinity of a DSB. Several lines of evidence led to the hypothesis that ␥-H2AX is essential for the the recruitment of repair/signaling proteins to DNA damage: (a) ␥-H2AX IRIF formation exhibits rapid kinetics that precedes repair factor assembly into IRIF [5,12]; (b) H2AX, and more precisely ␥-H2AX [37,38] is required for foci formation for numerous factors including 53BP1, NBS1, BRCA1 and MDC1 [12,35,39,40]; (c) ␥-H2AX physically interacts with NBS1, 53BP1 and MDC1 [35,38,41,42]. However, ␥-H2AX-mediated foci formation is not equivalent to factor recruitment [37].…”
Section: Race To the Breakmentioning
confidence: 99%
“…15,20,46,47 10 mg of each Ter/HR reporter ROSA26 targeting plasmid was linearized by Kpn I digest and introduced by electroporation to 2 £ 10 7 cells. Cells were seeded on plates prepared previously with puromycin-resistant feeders.…”
Section: Mouse Cell Lines and Cell Culturementioning
confidence: 99%